(3YeGO GdQVG HHjGf COH GdbVGs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3TQa GdOjf YjSi Hf YKeGf GdZRjs ((3TjN Hf Ydi Hf eMeO LYaQi s)
(3ChdgG (B:s
(3hHYO adeG cGf ai COH GdbVG ddYdGeI TQa GdOjf YjSi GdZRi GNJUQJg eMQQkG eY RjGOGJ MSfI hSejJg YeGO GdQVG HHjGf COH GdbVG s
(3BNQgG (B:s
(3ai UhQI Yde GdbGVi HeG PcQ PcQg ai HGH GdTgGOGJ Je GdcJGH HMeO Gddg hYhfg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B51s
Keywords: (3Gdabg GdTGaYjs